Orotracheal Intubation Training Module - Thomas Nicholas; Bradley Webb; Ben Boedeker (Association of American Medical Colleges, 2010)
Abstract This orotracheal intubation module is based on a PowerPoint presentation and was constructed to help educate medical students, residents, and any other medical personnel interested in learning how to intubate. It was developed in order to provide an additional component to our airway management course, and is featured on the Center for Advanced Airway Technology's website at the University of Nebraska Medical Center. The module contains video, photos, text, and audio narration, which demonstrates a stepwise approach to intubation. The Center for Advanced Airway Technology initially developed these resources to help educate medical students and residents rotating through anesthesia at the Nebraska Medical Center. They have since expanded their audience to the Worldwide Web. The authors are also looking at the feasibility of translating this module to other languages to reach a greater audience.